Traumatic hand amputations among children in Greece: epidemiology and prevention potential. Issue 5 (17th December 2011) - Panagopoulou, Paraskevi; Antonopoulos, Constantine N; Iakovakis, Ilias; Dessypris, Nick; Gkiokas, Andreas; Pasparakis, Dimitrios; Michelakos, Theodoros; Kanavidis, Prodromos; Soucacos, Panayotis N; Petridou, Eleni Th
Abstract : Background: Traumatic hand and finger amputations frequently lead to permanent disability. Objective: To investigate their epidemiological characteristics and estimate the prevention potential among children 0–14 years old, through a cross-sectional survey. Methods: Nationwide extrapolations were produced based on data recorded between 1996 and 2004 in the Greek Emergency Department Injury Surveillance System and existing sample weights. Incident and injury related characteristics were analysed to identify preventable causes. Results: Among 197 417 paediatric injuries, 28 225(14%) involved the hand and fingers resulting in 236 amputations (∼1% of hand injuries). The annual probability to seek emergency department care for a hand injury was 3%. The estimated incidence rate (IR) of hand amputations was 19.7/100 000 person-years. Over 50% concerned children 0–4 years old (male:female=2:1), peaking at 12–24 months. Male preschoolers suffered the highest IR (38.7/100 000). Migrant children were overrepresented among amputees. Of all amputations, 64% occurred in the house/garden and 14% in day-care/school/sports activities, usually between 08:00 and 16:00 (61%). Doors were the product most commonly involved (55% overall; 72% in day-care/school/gym) followed by furniture/appliances (15%) and machinery/tools (7%). Crushing was the commonest mechanism. Inadequate supervision and preventive measures were also frequently reported. 5% of the amputees were referred to specialised units for replantation/reconstructive surgery. Conclusions: The majority of paediatric hand and finger amputations could be prevented in Greece, particularly among preschoolers, by a single product modification, namely door closure systems, coupled with improved supervision. Paediatricians should incorporate this advice into their routine child-safety counselling. This country-specific profile supports the need for maintaining similar databases as an indispensable tool for assisting decision-making and preventing disabling and costly injuries.